2021
DOI: 10.1186/s12877-021-02164-3
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating foot assessment in the comprehensive geriatric assessment

Abstract: Background Foot problems are common in older adults and associated with poorer physical function, falls, frailty and reduced quality of life. Comprehensive Geriatric Assessment (CGA), a multidisciplinary process that is considered the gold standard of care for older adults, does not routinely include podiatry assessment and intervention in hospitalized older adults. Aims To introduce foot assessment to inpatient CGA to determine prevalence of foot … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 59 publications
0
1
0
Order By: Relevance
“…Previous studies have identified foot problems to be of a similarly high burden in outpatient populations, affecting 87% of community-dwelling older adults in one study by Menz and Lord [7]. Both inpatient and outpatient studies have also reported a high prevalence of inappropriate footwear in their respective cohorts [50, 51]. Specific deformities such as hammer and claw toes and hallux valgus were seen in fewer participants in the Falls and Balance clinic when compared to other studies, in which hallux valgus was recognised as the most common foot problem.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have identified foot problems to be of a similarly high burden in outpatient populations, affecting 87% of community-dwelling older adults in one study by Menz and Lord [7]. Both inpatient and outpatient studies have also reported a high prevalence of inappropriate footwear in their respective cohorts [50, 51]. Specific deformities such as hammer and claw toes and hallux valgus were seen in fewer participants in the Falls and Balance clinic when compared to other studies, in which hallux valgus was recognised as the most common foot problem.…”
Section: Discussionmentioning
confidence: 99%
“…Despite being a less comorbid, less frail, and more functionally independent cohort, foot problems were comparably common in older adults in this FBC when compared to inpatient populations of older adults [50]. Thus, it is likely that podiatry input is equally important in an outpatient cohort of comparably functionally independent individuals as it is in a hospital setting, where the acuity of disease is higher.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whilst literature on podiatry practice in reablement is limited, evidence suggests that older people represent the largest proportion of care provided by podiatrists in Australia and their attendance at podiatrists tends to be recurrent [20,21]. The link between foot problems in older age which reduce mobility and decrease quality of life has been well established [22][23][24][25][26][27][28][29][30][31]. Therefore, it is reasonable to assume that podiatrists are well placed to be integrated into reablement teams.…”
Section: Introductionmentioning
confidence: 99%